Fiscal Transfers, Income Inequality, and Human Development: Evidence from Central Kalimantan Province - Sarif Hidayat; Wiwin Zakiah; Alexandra Hokum (Institut Bisnis dan Informatika Kesatuan, 2025)
This study analyzes the impact of fiscal transfers from the central government and income inequality on human development in Central Kalimantan Province over the period 2020–2024. Despite steady increases in fiscal funds and improvements in human development indicators, the province continues to face challenges from persistent income inequality that limits equitable progress. Previous research often examines fiscal funds and inequality separately, leaving a gap in understanding their simultaneous effects at the local level. The objective is to examine how general allocation funds, special allocation funds, and the Gini index jointly influence the human development index using panel data from 13 regencies and 1 city. The analysis employs a fixed effect model selected after appropriate statistical tests. The results reveal that both general allocation funds and special allocation funds have significant positive effects on the human development index, with special allocation funds showing a slightly stronger contribution. In contrast, the Gini index exerts a significant negative effect, indicating that higher income inequality substantially hinders human development. The model explains 78 percent of the variation in the human development index. These findings highlight the importance of effective fiscal management combined with targeted strategies to reduce income inequality. Policymakers in Central Kalimantan should prioritize transparent use of fiscal transfers in education and health sectors while implementing inclusive programs to lower inequality, ensuring more equitable and sustainable human development across the province.